Baroque Historical Dances Lecture and Workshop by Mireia Frutos Fernandez : World Music History Lecture Series - Universiti Teknologi MARA, Faculty of Music (Universiti Teknologi MARA, 2018)
The lecture and workshop recognize some court dance movements from the Baroque era (1600-1750). The workshop covers two movements (Pas de bourrée and the Minuet). Musicians can identify the musical features of dance where each movement has different rhythmic patterns and significant characters. The experience gives exposure to musicians on the movements that can be interpreted into music.